2022
DOI: 10.1155/2022/5634724
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Pathway Alterations Offer Potential Biomarkers and Therapeutic Targets for Ovarian Cancer

Abstract: The mitochondrion is a very versatile organelle that participates in some important cancer-associated biological processes, including energy metabolism, oxidative stress, mitochondrial DNA (mtDNA) mutation, cell apoptosis, mitochondria-nuclear communication, dynamics, autophagy, calcium overload, immunity, and drug resistance in ovarian cancer. Multiomics studies have found that mitochondrial dysfunction, oxidative stress, and apoptosis signaling pathways act in human ovarian cancer, which demonstrates that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 184 publications
(194 reference statements)
0
21
0
Order By: Relevance
“…Mitochondrial dynamics are closely related to the activity of neuronal cells, but some studies have shown that phenotypic changes in cancer cells are also affected by mitochondrial dynamic defects ( Sehrawat et al, 2016 ; Shen and Zhan, 2022 ). The substances required for tumor metabolism include amino acids and are closely related to mitochondrial metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dynamics are closely related to the activity of neuronal cells, but some studies have shown that phenotypic changes in cancer cells are also affected by mitochondrial dynamic defects ( Sehrawat et al, 2016 ; Shen and Zhan, 2022 ). The substances required for tumor metabolism include amino acids and are closely related to mitochondrial metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that mitochondrial fusion increases ATP generation and fission contributes to mtDNA stress through mitochondrial dysfunction. 63 The imbalance of mitochondrial dynamics leads to mitochondrial DNA mutations and deletions, and these abnormalities have also been reported in endometriotic cells. 11 In fact, the mtDNA 16 189 variants and the combination of mtDNA 16 189 and 10 398 variants have been reported to be associated with endometriosis.…”
Section: Mitochondrial Dynamics In Endometriosismentioning
confidence: 99%
“…Changes in mitochondrial energy metabolism have recently been suggested as possible causes for chemoresistance and tumor recurrence in HGSOC (2,7,23,40,41). To further investigate the changes in mitochondrial function, we obtained nine surgically removed normal ovarian and ovarian tumor tissue biopsies from the Tissue Procurement Center at the Marshall University Edwards Comprehensive Cancer Center, Huntington, WV.…”
Section: Heterogeneity Of Mitochondrial Energy Metabolism In Ovarian ...mentioning
confidence: 99%